UMA METÁFORA VISUAL: DO OPACO À TRANSPARÊNCIA - AMBIENTES PLURAIS NA CULTURA ARTÍSTICA E ARQUITECTÓNICA CONTEMPORÂNEAS A VISUAL METAPHOR: FROM OPAQUE TO TRANSPARENCY – PLURAL SURROUND ENVIRONMENTS IN ARCHITECTURAL AND ARTISTIC CONTEMPORARY CULTURE - Guerreiro, Ana Santos (European Scientific Journal, ESJ, 2013)
The idea of”transparency” crosses epistemological, sociological, cultural and even political areas and it maintains, in contemporaneity, a privileged place for inquire and significance. Through the passage from opaque to transparency, by means of diverse and gradual degrees of translucence, it is possible to symbolise the creative process in contemporary art and architecture and its repercussions for a gnoseological domain. Interpreting transparency as a mediating and dynamic entity, we intend to research in modes of understanding for both its material (literal) and metaphorical (virtual) ‘use’ in art and architecture. These accomplish, by means of material choices and formal, functional and aesthetic transformations, a framework where it is possible to observe the passage from a crystalline state to an environmental one. The opacity/transparency duality addresses, through a plurality of meanings along time, the visible/invisible problem – or, in another reading, the one concerning appearance/meaning. Intrinsic question of both artistic and architectural creations and their meaning, transparency assumes a simultaneously dynamic and discrete statute, transcending what emerges from the work, and can be related to virtuality and even dissolution, from the visuality to others domains.